The directive liderchip in the management of organizational development (Review) (Revista científica Olimpia, 2018)
The present written report comprises the scientific basis in the management of organizational development. The novelty lies in the fact that it declares a new approach in this topic. It enfasizes the necessary interfunctional relationship that must be established among the members of the organization, as well as the improvement of the professional manner of acting and the professional competencies to fulfil the objectives proposed and a sosteinable development. To the report defining of directive leadership, it emphasise in the formation and development of directive conpetencies, taking as a support the performance of directive functions and the context of the directive´s professional acting.
Keywords: lidearship; management; organization; directive conpetencies